Strengthening Universities Around the World - El-Khawas, Elaine (International Higher Education, 2012)
In many countries, reform of university governance has introduced appointed leaders and external governing boards. The objective is to have more strategic and effective universities able to contribute to national development. This article offers evidence that improved governance has allowed several universities to more actively set and advance goals while overcoming constraints.